AUDIT MANAGEMENT TECHNOLOGY AND SYSTEMS INFORMACIÓNAUDITORÍA MANAGEMENT TECHNOLOGY AND INFORMATION SYSTEMS - Ramírez R., Guadalupe (2003)
This article outlines the use of computing audit as a tool to exert a suitable use of information thechnology, supported by applying legal regulations as well as international computing standards. In methodology, two basic features have been considered: both risk areas and control areas identification.